Effect of cisapride on postprandial gastro-oesophageal reflux. Issue 9 (September 1989) - Holloway, R H; Downton, J; Mitchell, B; Dent, J
Abstract : We studied the effect of cisapride on oesophageal motor function and postprandial gastro-oesophageal reflux in a randomised, double blind, placebo controlled crossover study. In 16 patients with symptomatic gastro-oesophageal reflux, cisapride 10 mg orally and placebo were studied on separate days according to identical protocols. Cisapride and placebo were given 30 minutes before a standard meal. Each study day was preceded by corresponding three day oral loading of cisapride (10 mg tds) or placebo. Lower oesophageal sphincter pressure, oesophageal body motility and oesophageal pH were monitored for 30 minutes before and three hours after the meal. Plasma cisapride concentrations were measured before and after dosing on both study days. With cisapride treatment, the plasma cisapride levels ranged from 48.1 (5.0) to 75.9 (6.9) ng/ml. Plasma levels were undetectable during placebo treatment. Cisapride enhanced acid clearance but had no significant effect on the duration of acid exposure, the rate of reflux episodes, the pattern of lower oesophageal sphincter pressure associated with the reflux episodes, basal lower oesophageal sphincter pressure or oesophageal peristalsis. These findings do not suggest a major role for cisapride, at the dosage tested, for the control of troublesome postprandial gastro-oesophageal reflux.